Expression of palmitoyl transferases in brain structures of mice genetically predisposed to depressive-like behavior - E. M. Kondaurova; T. V. Ilchibaeva; A. S. Tsybko; Е. G. Ponimaskin; V. S. Naumenko (Вавиловский журнал генетики и селекции)
Most G-coupled receptors undergo posttranslational modifications. Among these modifications is S-palmitoylation, carried out by specialized enzymes palmitoyl transferases. Palmitoylation is the covalent attachment of a long-chain fatty acid, palmitate, to cysteine residues. It can influence receptor stability, transportation, and function. Obviously, malfunction of G-protein coupled receptors can cause various psychic disorders, including depression. However, no association between palmitoyl transferases and depressive-like behavior has been found hitherto. There is no information on brain structure specific features of palmitoyl transferase expression either. Here we investigate the expression of ZDHHC5, ZDHHC9, and ZDHHC21 palmitoyl transferases in brain structures of ASC mice with genetic predisposition to depressive-like behavior in comparison with “nondepressive” CBA mice. Several brain region-specific features were detected in the immunodetection of palmitoyl transferase proteins. Western blot of the ZDHHC5 protein in the midbrain revealed two bands at 75 kDa and 55 kDa. Immunodetection of ZDHHC21 palmitoyl transferase revealed two bands. One of them was visualized at 27 kDa in the frontal cortex and midbrain. The other, at 32 kDa in the hippocampus. Probing for ZDHHC9 also showed two bands in each of the midbrain and hippocampus, at 46 and 41 kDa. However, the expression of all investigated palmitoyl transferases in ASC mice with depressive-like behavior was almost identical to those in CBA mice. Thus, it was the first detection of brain region-specific features of the expression of investigated palmitoyl transferases. However, the study demonstrates that the genetic predisposition to depression-like behavior in ASC mice is not associated with changes in ZDHHC5, ZDHHC9, or ZDHHC21 palmitoyl transferase expression.